Community Reporting System: Road Violation - R. Roslan, M.; Ahmad Zabidi, Suriza (Institute of Advanced Engineering and Science, 2019)
In the era of internet and wireless, an online community reporting system that is easy to use and hustle free is much needed to allow the user to place a misconduct report to the relevant authority. The available system is inefficient and time-consuming since mostly are using web-based which makes the user unwilling to make a report to the authority. The objective of this project is to design a system using android application that is cost-effective and easy to use. The scope of this project is on the road violation reporting system. The outcome of the system will provide a user with an easy reporting system and also the authority can manage the report easily. The development of the system is expected to enhance the reporting system and betterment for the community as well as the authority as a whole.